2020
DOI: 10.1021/acsami.0c09656
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Critical Role of Melt-Spinning Atmosphere in Enhancing the Thermoelectric Performance of p-Type Bi0.52Sb1.48Te3 Alloys

Abstract: Melt spinning has proven effective in maintaining chemical homogeneity and introducing multiscale microstructures that can reduce the lattice thermal conductivity and consequently enhance the thermoelectric performance of consolidated bulk materials. In this work, p-type Bi0.52Sb1.48Te3 bulk alloys are fabricated by melt spinning (MS) followed by subsequent plasma activated sintering (PAS). The influence of different MS atmospheres (air, Ar, N2, and He) on the morphologies of MS ribbons and the thermoelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…As a result, the obtained ZT of PbTe was found to be 0.8 at 300 K. The thermoelectric properties of Cu-doped p-type Bi 0.5 Sb 1.5 Te 3 were investigated to determine the intrinsic excitation effect in BST material, resulting in the highest ZT of 1.0 at 450 K. 156 The layered compound BiMnTe 4 was found to be a p-type semiconductor with a high Seebeck coefficient at 300 K (168 μV∕K ). Also, in nanostructured Bi 2 Te 3 /MnTe 2 , the ZT was found to be 0.26 at 480 K. 157 The sintered bulk materials of p-type Bi 0.52 Sb 1.48 Te 3 prepared using melt spinning and rapid sintering were found to depend on thermal conductivity of ambient gases with enhancement in ZT value of about 1.09 at 340 K. 158 To control the crystallographic preferred orientation, melt spinning method has been applied for CHI 3 -doped Bi 2 Te 2.4 Se 0.6 alloys with an optimized frequency of 300 rpm with ZT of 1.02 at 400 K. 119 The outstanding homogeneity and reproducibility by varying the stoichiometry have played a crucial role in the transport properties of p-type Bi x Sb 2−x Te 3 prepared by melt spinning. 159 The bulk materials of p-type Bi 0.52 Sb 1.48 Te 3 were synthesized by Yun et al, 160 and it was observed that an argon atmosphere could effectively inhibit heat loss and suppress the sublimation of tellurium.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the obtained ZT of PbTe was found to be 0.8 at 300 K. The thermoelectric properties of Cu-doped p-type Bi 0.5 Sb 1.5 Te 3 were investigated to determine the intrinsic excitation effect in BST material, resulting in the highest ZT of 1.0 at 450 K. 156 The layered compound BiMnTe 4 was found to be a p-type semiconductor with a high Seebeck coefficient at 300 K (168 μV∕K ). Also, in nanostructured Bi 2 Te 3 /MnTe 2 , the ZT was found to be 0.26 at 480 K. 157 The sintered bulk materials of p-type Bi 0.52 Sb 1.48 Te 3 prepared using melt spinning and rapid sintering were found to depend on thermal conductivity of ambient gases with enhancement in ZT value of about 1.09 at 340 K. 158 To control the crystallographic preferred orientation, melt spinning method has been applied for CHI 3 -doped Bi 2 Te 2.4 Se 0.6 alloys with an optimized frequency of 300 rpm with ZT of 1.02 at 400 K. 119 The outstanding homogeneity and reproducibility by varying the stoichiometry have played a crucial role in the transport properties of p-type Bi x Sb 2−x Te 3 prepared by melt spinning. 159 The bulk materials of p-type Bi 0.52 Sb 1.48 Te 3 were synthesized by Yun et al, 160 and it was observed that an argon atmosphere could effectively inhibit heat loss and suppress the sublimation of tellurium.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…178 Hamawandi et al 179 Copyright (2020) with permission from the American Chemical Society. 158 two forms of bismuth telluride synthesized by a hydro and polyol method, where the final forms of samples prepared by both methods were subjected to spark plasma sintering. Using the hydro method, the electrical conductivity values, Seebeck coefficient, thermal conductivity, and ZT were found to be 9.6 × 10 5 S/m, −149 µV/K, 0.9 W/ mK, and 0.88, respectively, at 373 K, whereas they were 9.2 × 10 5 S/m, −148 µV/K, 0.86 W/mK, and 0.86, respectively, at 373 K using the polyol method (Fig.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…Especially, for amorphous metallic compounds and due to their capacity of producing nanograins, melt-spinning has been utilized since the early 1980s. 161 Several intermetallic phases such as FeCoNiAlTi HEI 162 for HER and Cu/Al 7 Cu 4 Ni@Cu 4 Ni 163 and NiIrRuAl NPNWs 164 for overall water splitting have been fabricated via this facile approach to fine-tune their properties for efficient catalysis ( Fig. 5 ).…”
Section: Chemical Synthetic Strategies Of Intermetallicsmentioning
confidence: 99%
“…This type of conversion from thermal heat to electricity possesses a lot of advantages, such as silent mode, no noise and less pollution, which has also triggered the development of various niche applications, including radioisotope thermoelectric (TE) generators (TEGs) for the space exploration, for example, National Aeronautics and Space Administration's Voyager 1 and 2. However, all these applications put forward strict requirements for energy conversion efficiency, and traditionally, high-performance inorganic semiconducting materials, such as bulk Bi 2 Te 3, SnSe, and PbTe [1][2][3][4][5][6], have been extensively studied and fabricated into the TEGs.…”
Section: Introductionmentioning
confidence: 99%